Performance of Photoscreener in Adults - Güler Alış, Meryem; Alış, Abdülkadir (Cerrahpaşa Medical Journal, 2022)
Objective: To investigate the performance of the photoscreener (Plusoptix A12, GmbH, Nuremberg, Germany) in adults by comparing it with a classic table top autorefractometer (ARK-1 Auto Ref-Keratometer, Nidek, Japan). Methods: A total of 100 eyes (right) of 100 patients aged 18-55 years were prospectively evaluated. Patients’ refraction values obtained with the Plusoptix A12 as a photoscreener in monocular and binocular conditions were compared with those of the classic table top autorefractometer. The correlations of spherical equivalent differences in regard to axial length, anterior chamber depth, and central corneal thickness were examined. Results: When Plusoptix A12 and autorefractometer values in the binocular condition were compared, no significant difference was observed in spherical values, spherical equivalent values, J0, or J45 values. Intraclass correlation coefficient values showed a good degree of agreement between the 2 devices. When Plusoptix A12 values were measured monocularly and autorefractometer values were compared, spherical equivalent, spherical, and cylindrical values were found to be statistically different, although intraclass correlation coefficient values were compatible in both devices. There was no difference between J0 and J45 values. A weak positive correlation was observed between the spherical equivalence differences and anterior chamber depth and axial length. Conclusion: Plusoptix A12 values measured under binocular conditions and autorefractometer values are compatible and have similar results in the detection of simple myopia without astigmatism, simple hyperopia without astigmatism, and emmetropia in adults. Therefore, Plusoptix can be used to diagnose low-level simple myopia and hyperopia and to detect emmetropia during a pandemic period. However, it should not be forgotten that autorefractometry is the gold standard for higher and/or complex astigmatism and refractive errors. Cite this article as: Güler Alış M, Alış A. Performance of photoscreener in adults. Cerrahpaşa Med J. 2022;46(2):144-150.